Pregabalin and other antiepileptic drugs in chronic neuropathic pain - Paolo Marchettini (Publiediting, 2017)
Chronic pain resulting from nervous system injury is, in almost all cases, difficult to treat. In 1995 the first trial on the efficacy of gabapentin for neuropathic pain appeared. In 2004 pregabalin was introduced, approved as adjunctive therapy in epilepsy and the treatment of generalized anxiety disorder and peripheral and central neuropathic pain in adults (for example pain originating from post-herpetic neuralgia, neuropathy associated with neoplastic disease, post-stroke pain or spinal paralysis, polyneuropathy, multineuropathy, mononeuropathy, and painful diabetic neuropathy). Studies comparing the two drugs indicate a greater power of action of pregabalin with a dose efficacy ratio of 3 to 1. This allows pregabalin to be released at lower doses without the need of lengthy initial titration to achieve therapeutic range. The bioavailability of pregabalin is constant while that of gabapentin decreases with the dose; gabapentin bioavailability at 1600 mg is only 27% while for pregabalin bioavailability is > 90% at all doses. Pregabalin in direct comparison has proved clinically more effective than gabapentin and is also effective in patients unresponsive to gabapentin. Gabapentin absorption takes place only in the small intestine while that of pregabalin even in the ascending portion of the colon. This leads to a higher risk of gabapentin interactions with drugs affecting small intestine motility, such as opioids, often associated in pain therapy. For the same reason, patients with bowel resections benefit best from treatment with pregabalin.